INDONESIAN CULTURAL DIPLOMACY THROUGH THE INDONESIAN CULTURAL CENTER IN TIMOR LESTE - Fitri Yanti Laia; Den Yealta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Culture is an object that can be used as an attraction to attract the interest of the international community to get to know Indonesia better. Besides being the identity of a country, culture is an important instrument in soft diplomacy. Culture can also be used as a means of diplomacy by a country, especially Indonesia, which has a variety of cultures. This study uses a constructivism perspective. The assumptions that form the basis of this perspective are social interactions between individuals in society. This research is analyzed using nation-state analysis and using the theory of cultural diplomacy which is a way for a country to introduce and build a positive image of a country in an international view. The method in this study uses qualitative methods. The results of this study indicate an increase in Timor Leste tourist visits to Indonesia through the Indonesian Cultural Center program. Through the program the Indonesian Cultural Center also enhances bilateral relations between Indonesia and Timor Leste in various aspects, economic, social, cultural and also education. Keywords: Culture, Diplomacy, Indonesian Cultural Center, Cultural Diplomacy